Mercer Green Johnston papers - Johnston, Mercer Green, 1868-1954.
Correspondence, diaries, sermons, notebooks, poems, prayers, financial records, autobiographical papers, pamphlets, periodicals, clippings, scrapbooks, photographs, and other papers pertaining to Johnston's career as an author, educator, and clergyman. Documents his work as Episcopal minister in the U.S. and the Philippines including his years as rector of Trinity Church, Newark, N.J.; chairman of the National Progressive Headquarters, Baltimore, Md., and Peoples' Legislative Service, Washington, D. C.; director of the National Citizens Committee on Relations with Latin America; and New Deal official with the U.S. Rural Electrification Administration and other agencies. Also documents his work for the Young Men's Christian Association during World War I and as a freelance writer on economic, labor, political, and social issues. Correspondents include William Edgar Borah, Charles Henry Brent, Bronson M. Cutting, Eugene V. Debs, Elisabeth Coit Gilman, James Steptoe Johnston, Judson King, Robert M. La Follette, W. Jett Lauck, George Fort Milton, George William Norris, G. Bromley Oxnam, William Thomas Rawleigh, Oswald Garrison Villard, Thomas James Walsh, and Burton K. Wheeler.
Educator, Episcopal clergyman, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Borah, William Edgar, -- 1865-1940 -- Correspondence; Brent, Charles Henry, -- 1862-1929 -- Correspondence; Cutting, Bronson M., -- 1888-1935 -- Correspondence; Debs, Eugene V. -- 1855-1926 -- Correspondence; Gilman, Elisabeth Coit, -- 1867-1950 -- Correspondence; Johnston, James Steptoe, -- 1843-1924 -- Correspondence; King, Judson, -- 1872-1958 -- Correspondence; La Follette, Robert M. -- 1855-1925 -- Correspondence; Lauck, W. Jett -- 1879-1949 -- Correspondence; Milton, George Fort, -- 1894-1955 -- Correspondence; Norris, George William, -- 1861-1944 -- Correspondence; Oxnam, G. Bromley -- 1891-1963 -- Correspondence; Rawleigh, William Thomas, -- 1870-1951 -- Correspondence; Villard, Oswald Garrison, -- 1872-1949 -- Correspondence; Walsh, Thomas James, -- 1859-1933 -- Correspondence; Wheeler, Burton K. -- 1882-1975 -- Correspondence; United States. -- Rural Electrification Administration; Episcopal Church -- Clergy; Episcopal Church -- Philippines; Episcopal Church -- United States; National Citizens Committee on Relations with Latin America; National Progressive Headquarters; People's Legislative Service; Trinity Church (Newark, N.J.); Labor -- United States; New Deal, 1933-1939.; Progressivism (United States politics); World War, 1914-1918 -- War work -- Young Men's Christian associations; Latin America -- Foreign relations -- United States; United States -- Economic conditions -- 20th century; United States -- Foreign relations -- Latin America; United States -- Politics and government -- 1901-1953.; United States -- Social conditions -- 20th century; Authors; Clergy; Educators